Educational comic: EKSIS CERMIN SI IMUT, as efforts to improve dental and oral health knowledge in Elementary School 12 Kapopposang Island - Ansyari Muis; Erwin Gunawan; Pharadiba Pharadiba; Febriansyah M. Ashar; Irene E. Rieuwpassa (Journal of Dentomaxillofacial Science, 2020)
Objective: Dental and oral health knowledge is one of the efforts to prevent and cope with dental and oral health problems. The target of this student creativity program is elementary school students in Kapopposang island from third grade to fifth grade.Material and Methods: The method of implementation of this activity is the presentation of data, preparation of implementation, implementation of activities, evaluation by using pretest-postest and preparing reports.Results: The average value data pre-test and post-test were analyzed using paired t test with SPSS 24 for Windows. The data shows significant results value p (0.000)< 0.05.Conclusion: The conclusion of this activity can be obtained that the Comic Eksis Cermin Si Imut is effective in increasing students knowledge of class III, IV, and V SDN 12 Kapopposang Island.